The labour market, immigration and the building of Dubai - Connell, Julia; Burgess, John (International Employment Relations Association, 2011)
Dubai has evolved from a sparsely populated desert region on the Arabian Gulf to a dynamic and fast growing city. The boom in construction and services has been built upon a large immigrant labour force with a labour market that is highly segregated - firstly between local and expatriate workers, and secondly among the expatriate workers depending on whether they are categorised as professional, construction or service sector workers. Despite the rapid growth and manifestations of modernity in Dubai, stories have emerged concerning the violation of human rights particularly with respect to contracted migrant workers. Despite its rapid transformation Dubai does not have in place the institutions or infrastructure that support and protect fundamental labour standards. Where there are unregulated migrant programs (as in Dubai), workers are potentially subject to exploitation. This paper examines the labour market and immigration in Dubai and considers whether growth has been compromised by promoting fundamental labour standards and whether this is likely to change post GFC.